2015
DOI: 10.1074/jbc.m114.624700
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-873 (MiRNA-873) Inhibits Glioblastoma Tumorigenesis and Metastasis by Suppressing the Expression of IGF2BP1

Abstract: Background: Recent research has uncovered tumor-suppressive and oncogenic potential of miRNAs. Results: miR-873 suppresses the proliferation, migration, and invasiveness of GBM cells by targeting IGF2BP1. Conclusion: Down-regulation of miR-873 results in overexpressed IGF2BP1, contributing to tumorigenesis of GBM cells. Significance: The identification of tumor suppressor miR-873 and its oncogenic target IGF2BP1 in GBM cells is potentially valuable for cancer diagnosis and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 37 publications
0
71
1
Order By: Relevance
“…However, it plays different roles in different tumors. miRNA-873 promotes the proliferation and migration of tumor cells by repressing Src in lung adenocarcinoma [14] but acts as a tumor suppressor in glioblastoma [13] and ovarian cancer [16]. However, little is known about the role of miRNA-873 in HCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it plays different roles in different tumors. miRNA-873 promotes the proliferation and migration of tumor cells by repressing Src in lung adenocarcinoma [14] but acts as a tumor suppressor in glioblastoma [13] and ovarian cancer [16]. However, little is known about the role of miRNA-873 in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-873 inhibits ER (estrogen receptor)-α activity and cell growth by targeting CDK3, mediating tamoxifen resistance [15]. miRNA-873 is downregulated in glioblastoma, inhibiting cell proliferation, migration and invasion and inducing apoptosis through suppressing the expression of IGF2BP1 [13]. However, it is upregulated in lung adenocarcinoma, acting as an oncogene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also an oncofetal protein, IGF2BP1 is commonly detected in several tumors. Its effects upon growth are variable with speculation of both oncogenic as well as tumorsuppressive functionality (31,(44)(45)(46) based upon the cellular context of its expression. As shown here, overexpression of IGF2BP1 in the committed erythroblasts did not prevent their maturation or enucleation in ex vivo cultures.…”
Section: Bcl11a Is Posttranscriptionally Regulated In Igf2bp1 Overexpmentioning
confidence: 99%
“…In a recent study, miR-873 was shown to be downregulated in breast tumors and to play a tumor suppressor role by targeting cyclin-dependent kinase 3, leading to the inhibition of ER-α activity and the suppression of breast cancer cell proliferation and tumor growth [31]. Insulin-like growth factor 2 mRNA binding protein 1 (IGFBP1) was identified as a target of miR-873 in glioblastoma [32]. IGFBP1, which is produced at high levels in the human endometrium, has been suggested as a marker of EP [33, 34].…”
Section: Discussionmentioning
confidence: 99%